2013
DOI: 10.1002/adsc.201300630
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed α‐Aminoxylation of Ketones with 2,2,6,6‐Tetramethylpiperidine‐1‐oxyl (TEMPO)

Abstract: An efficient copper-catalyzed a-aminoxylation of ketones with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) is presented for the synthesis of 2-aryloxy-1-aryl-2-(2,2,6,6-tetramethylpiperidin-1-yl-A C H T U N G T R E N N U N G oxy)ethanones in moderate to excellent yields. It is noteworthy that the copper/iron (Cu/Fe) catalyst can be recovered and reused several times with high catalytic reactivity.Scheme 2. Utilizations of products 2a and 2p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…With substrate 1, competing alcohol oxidation increased as the catalyst loading decreased, 25 but even using 20 mol % 5* with 2 and 3 led to significant formation of byproducts resulting from substrate formylation and radical coupling with the TEMPO cocatalyst. Similar products have been observed for the CAN-catalyzed α-aminoxylation of ketones 32,33 and copper-catalyzed aminoxylation of ketones 34 and hydrocarbons. 35 Additionally, Hayton and co-workers proposed formation of an α-keto radical in a ketone (similar to compound 12), which is rapidly quenched by TEMPO following a one-electron concerted proton−electron transfer to produce the TEMPO-adduct.…”
Section: ■ Resultssupporting
confidence: 78%
“…With substrate 1, competing alcohol oxidation increased as the catalyst loading decreased, 25 but even using 20 mol % 5* with 2 and 3 led to significant formation of byproducts resulting from substrate formylation and radical coupling with the TEMPO cocatalyst. Similar products have been observed for the CAN-catalyzed α-aminoxylation of ketones 32,33 and copper-catalyzed aminoxylation of ketones 34 and hydrocarbons. 35 Additionally, Hayton and co-workers proposed formation of an α-keto radical in a ketone (similar to compound 12), which is rapidly quenched by TEMPO following a one-electron concerted proton−electron transfer to produce the TEMPO-adduct.…”
Section: ■ Resultssupporting
confidence: 78%
“…Moreover, Tan4d and Koike4f respectivly reported photocatalyst catalyzed α‐aminoxylation of 1,3‐dicarbonyl compounds with TEMPO in the presence of photoredox catalysts such as organic dyes or iridium complexes. In 2013, Li and co‐workers5o developed a reusable Cu/Fe catalyst for α‐aminoxylation reactions between ketones with TEMPO. More recently, Jiao and co‐workers6f first demonstrated a CAN‐catalyzed α‐aminoxylation of 1,3‐dicarbonyl compounds with TEMPO [Scheme , Eq.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of our investigations we found that little excess of an amine (5-10 mol%) increased the water formation showing that the process of amide synthesis proceeded not as a thermal dehydration of carboxylic acid salt but as an addition of an amine at the carbonyl group of the salt (Scheme 2). The formation of the coordination bond between metallic copper and the oxygen of carbonyl or ester groups has been suggested earlier in [20].…”
mentioning
confidence: 74%